Synthesis and in vitro antineoplastic evaluation of silver nanoparticles mediated by Agrimoniae herba extract - Qu D (Dove Medical Press, 2014)
Ding Qu,1,* Wenjie Sun,1,2,* Yan Chen,1,2 Jing Zhou,1 Congyan Liu11Key Laboratory of New Drug Delivery System of Chinese Materia Medica, Jiangsu Provincial Academy of Chinese Medicine, 2Department of Pharmaceutics, School of Pharmacy, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China*These authors contributed equally to this workAbstract: A rapid synthesis of silver nanoparticles (AgNPs) using Agrimoniae herba extract as reducing agent and stabilizer (A. herba-conjugated AgNPs [AH-AgNPs]) were designed, characterized, and evaluated for antitumor therapy feasibility. In this study, critical factors in the preparation of silver nanoparticles, including extraction time, reaction temperature, the concentration of AgNO3, and A. herba extract amount, were investigated using ultraviolet-visible spectroscopy. AH-AgNPs with well-defined spherical shape, homogeneous distributional small size (30.34 nm), narrow polydispersity index (0.142), and high negative zeta potential (−36.8 mV) were observed by transmission electron microscopy and dynamic light scattering. Furthermore, the results of X-ray diffraction and Fourier-transform infrared spectroscopy further indicated successful preparation of AH-AgNPs. Acceptable long-term storage stability of AH-AgNPs was also confirmed. More importantly, AH-AgNPs displayed significantly higher antiproliferative effect against a human lung carcinoma cell line (A549 cells) compared with A. herba extract and bare AgNPs prepared by sodium citrate. The half-maximal inhibitory concentrations of AH-AgNPs, bare AgNPs, and A. herba extract were 38.13 µg · mL-1, 184.87 µg · mL-1, and 1.147 × 104 µg · mL-1, respectively. It is suggested that AH-AgNPs exhibit a strong antineoplastic effect on A549 cells, pointing to feasibility of antitumor treatment in the future.Keywords: rapid synthesis, Agrimoniae herba extract, silver nanoparticles, A549 cells, antitumor